Branding: Representation, Communication, and Simulation - Wijaya, Bambang Sukma (Jobmark: Journal of Branding and Marketing Communication, 2019)
Branding in contemporary society reflects a fundamental transformation from mere product representation to a semiotic system that constructs social reality. This article examines branding through three conceptual dimensions using interdisciplinary approaches. At the level of representation, brands function as signifiers that reflect product identity and values. In the communicative dimension, brands act as a message system and a medium of social and emotional interaction that builds symbolic attachment between producers and consumers. In the simulation stage, brands operate as forms of hyperreality, creating fictitious realities through mediated imagery and narratives. The study argues that branding has become an ideological arena where value, identity, and power are produced and negotiated. By adopting a critical understanding of these three dimensions, this article reveals how branding not only represents the world but also participates in the creation and simulation of cultural reality in global consumer society.